Aspergillus colonization in patients with bronchogenic carcinoma. (May 2014) - Ali, Sana; Malik, Abida; Bhargava, Rakesh; Shahid, Mohammad; Fatima, Nazish
Background: Aspergillus antigens such as galactomannan antigen, a cell wall polysaccharide, can be detected in patient's serum or bronchoalveolar lavage. To study the prevalence of Aspergillus infection in patients with bronchogenic carcinoma, we measured galactomannan antigen in serum and bronchoalveolar lavage samples of patients with bronchogenic carcinoma. Methods: The study was conducted on 45 bronchogenic carcinoma patients. The diagnosis of lung cancer was confirmed by bronchoscopy, histopathological and radiological examinations. Bronchoalveolar lavage fluid collected from each patient by fiberoptic bronchoscopy was subjected to direct microscopy and culture on Sabouraud's dextrose agar and Czapek-Dox agar, and Aspergillus galactomannan antigen was measured in serum and bronchoalveolar lavage samples. Results: The majority of patients were male (93.3%) in the age group 51–60 years, 88.9% were addicted to gutka chewing, and 82.1% were addicted to smoking. Most patients complained of cough (73%) and shortness of breath (51.1%). Squamous cell carcinoma (64.4%) was the most common malignancy, followed by adenocarcinoma (13.3%). On culture of bronchoalveolar lavage samples, 35.5% showed growth of Aspergillus spp. ( Aspergillus fumigatus in 17.8%, Aspergillus flavus in 13.3%, and Aspergillus niger in 4.4%). Galactomannan antigen was detected in 58.3% of bronchoalveolar lavage samples and 47.2% of serum samples. Conclusions: There is a high prevalence of aspergillosis in patients with lung carcinoma, especially among smokers and gutka chewers.